Age-related impairments on one hippocampal-dependent task predict impairments on a subsequent hippocampal-dependent task - Curlik, Daniel M; Weiss, Craig; Nicholson, Daniel A; Disterhoft, John F (Behavioral neuroscience, 2014)
Age-related cognitive impairments are particularly prevalent in forms of learning that require a functionally intact hippocampal formation, such as spatial and declarative learning. However, there is notable heterogeneity in the cognitive abilities of aged subjects. To date, few studies have determined whether age-related impairments on one learning task relate to impairments on different learning tasks that engage overlapping cognitive processes. Here, we hypothesized that aged animals that were impaired on 1 hippocampal-dependent behavioral procedure would be impaired on a second hippocampal-dependent procedure. Conversely, aged animals that were unimpaired on 1 hippocampal-dependent task would be unimpaired with a subsequent hippocampal-dependent form of learning. To test these hypotheses, we trained young (2-3 months old) and aged (28-29 months old) F344XBN male rats with trace eyeblink conditioning, followed by the Morris water maze. Half of aged rats were impaired during trace conditioning. Nearly half of aged animals were also impaired during water maze probe testing. Performance during trace conditioning correlated with performance during water maze testing in aged animals. Further analyses revealed that, as a group, aged animals that were impaired on 1 hippocampal-dependent task were impaired on both tasks. Conversely, aged animals that were unimpaired on 1 task were unimpaired on both tasks. Together, these results suggest that aged-related impairments on 1 hippocampal-dependent task predict age-related impairments on a second hippocampal-dependent procedure. These results have implications for assigning personalized therapeutics to ameliorate age-related cognitive decline.